Motivação de adolescentes para começar e parar de fumar e fatores associados: estudos embasados em teorias de mudança de comportamento - Rios, Leonardo Essado (2020)
Introduction: Smoking is a chronic disease caused by nicotine dependence, and a risk factor for several general and oral health problems. Multiple factors have been linked to smoking during adolescence, including psychosocial indicators. At the same time, the Behaviour Change Science has advanced in identifying the three essential elements of the mental motivational system that prompts smoking initiation and cessation: beliefs, desires, and intentions. However, the relationships between these factors need to be better understood in the adolescent population. Objective: To investigate the motivation of adolescent students to start and stop smoking based on Behaviour Change Theories and associated factors. Methods: A systematic review of the literature with meta-analysis, and three cross-sectional analytical studies were carried out. Adolescents aged 12 to 19 years were the target population. In the review, a systematic search for eligible studies was conducted on scientific bases by previously calibrated reviewers, who selected and evaluated studies about the intention of adolescents to quit smoking based on the Transtheoretical Model of Stages of Change. In the cross-sectional studies, the data were collected in federal schools of a Brazilian Midwest state. A self-administered questionnaire was used, containing: a) questions based on the Prime Theory of Motivation that measured desires, beliefs and intentions related to smoking initiation and cessation, b) psychosocial variables through validated scales of Sense of Coherence (SOC) and Duke University Religion Index (DUREL), and c) questions about adolescents' belief regarding the benefit of smoking cessation interventions in medical and dental services. Poisson or Logistics regressions were used in the statistical analysis. Results: Among the participants in the systematic review (n=6469), 41% of smokers had no intention of quitting smoking, which was associated with more unfavourable characteristics in relation to smoking, such as lower decisional balance and self-efficacy (p<0.05). In the cross-sectional analyses (n=3034), most smokers (57%) did not want to, nor intended to quit smoking, and approximately 6% of the non-smokers had the highest level of motivation to start (simultaneous presence of desire, belief, and intention). Among the non-smokers, an inverse association was observed between the motivation to start smoking and the SOC, so that for each increase of one unit in the SOC score, the probabilities of desire to smoke, belief in the benefit of the habit, and intention to smoke in the future decreased by three, three and five times, respectively. Similarly, for each unit increased in scores for Organizational, Non-Organizational, and Intrinsic Religiosity, the likelihood of motivation to start smoking decreased by 23, 23 and 15 times, respectively. Among the smokers, an increase in the Intrinsic Religiosity score increased the motivation to quit by 1.13 times. Compared to those unmotivated to quit smoking, the motivated ones had a greater belief in the benefit of interventions for smoking cessation in health services (p <0.05). Conclusion: The proportion of adolescents motivated to start or stop smoking was low and associated with psychosocial factors, which could be considered as potential influences of anti-smoking interventions for this population.